The clinical and pathological relevance of waxy casts in urine sediment. Issue 1 (31st December 2022) - Xu, Damin; Li, Jingzi; Wang, Suxia; Tan, Ying; Liu, Ying; Zhao, Minghui
Abstract: Although casts in urine may imply the underlying pathogenesis and the diagnosis, the waxy cast is poorly understood yet. We aim to investigate the association between waxy casts and clinicopathological indices. Patients undergone renal biopsy and urine sediment examination were enrolled. Waxy casts referred to those presented with a homogeneous melted wax appearance and pre-waxy casts referred to those in which one or more segments demonstrated a waxy-cast appearance. Multivariable logistic regression was used to assess the factors associated with waxy casts. In 1282 patients, the detection rate of waxy casts was 26.3%. If either waxy or pre-waxy cast was considered as a diagnostic marker for renal insufficiency (eGFR < 60 ml/min/1.73 m 2 ), the sensitivity was 0.58 and the specificity was 0.88. If the only waxy cast was considered as the diagnostic marker, the sensitivity was 0.29 and the specificity was 0.97. The patients with waxy or pre-waxy casts had higher blood pressure, more proteinuria, and worse renal function. Waxy or pre-waxy cast was independently associated with eGFR (odds ratio: 0.73 per 10 mL/min/1.73 m 2 increase, 95% confidence interval: 0.69–0.77, p  < 0.001), proteinuria (odds ratio: 1.07 per 1 g/day increase, 95% confidence interval: 1.03–1.10, p  < 0.001) and pathological lesions. Waxy or pre-waxy casts are closely related to impaired renal function. Their presence is a specific indicator of renal insufficiency but is not sensitive enough.